Dissemination of Orientia tsutsugamushi, a Causative Agent of Scrub Typhus, and Immunological Responses in the Humanized DRAGA Mouse - Jiang, Le; Morris, Erin K.; Aguilera-Olvera, Rodrigo; Zhang, Zhiwen; Chan, Teik-Chye; Shashikumar, Soumya; Chao, Chien-Chung; Casares, Sofia A.; Ching, Wei-Mei (Frontiers in Immunology, 2018)
Scrub typhus is caused by Orientia tsutsugamushi, an obligated intracellular bacterium that affects over one million people per year. Several mouse models have been used to study its pathogenesis, disease immunology, and for testing vaccine candidates. However, due to the intrinsic differences between the immune systems in mouse and human, these mouse models could not faithfully mimic the pathology and immunological responses developed by human patients, limiting their value in both basic and translational studies. In this study, we have tested for the first time, a new humanized mouse model through footpad inoculation of O. tsutsugamushi in DRAGA (HLA-A2.HLA-DR4.Rag1KO.IL2RcKO.NOD) mice with their human immune system reconstituted by infusion of HLA-matched human hematopoietic stem cells from umbilical cord blood. Upon infection, Orientia disseminated into various organs of DRAGA mice and resulted in lethality in a dose-dependent manner, while all C3H/HeJ mice infected by the same route survived. Tissue-specific lesions associated with inflammation and/or necrosis were observed in multiple organs of infected DRAGA mice. Consistent with the intracellular nature of Orientia, strong Th1, but subdued Th2 responses were elicited as reflected by the human cytokine profiles in sera from infected mice. Interestingly, the percentage of both activated and regulatory (CD4+FOXP3+) human T cells were elevated in spleen tissues of infected mice. After immunization with irradiated whole cell Orientia, humanized DRAGA mice showed a significant activation of human T cells as evidenced by increased number of human CD4+ and CD8+ T cells. Specific human IgM and IgG antibodies were developed after repetitive immunization. The humanized DRAGA mouse model represents a new pre-clinical model for studying Orientia-human interactions and also for testing vaccines and novel therapeutics for scrub typhus.